A study of employee performance among civil servants in Malaysia - Lim, Song Huat (2019)
The performance of civil service is concerning issue in Malaysia. Every year, the emolument for paying civil servants has taken our major portion in operating expenditure. Therefore, the performance of civil servants has been the questioning issue by the public whether the taxpayers’ money are being worth paid which lead to the conduct of this research. In the proposed research model, the independent variables tested were “compensation & rewards”, “working environment”, “self-development”, “empowerment” and “job satisfaction” with “motivation” as mediator. The main aim of this research is to study the parameters which affect the performance of civil servants in Malaysia. The target respondents are civil servants working in Putrajaya and Kuala Lumpur. A total of 303 questionnaires have been collected from data gathering. The data were analyzed by using SmartPLS version 3. The modules conducted for this research were frequency analysis, internal consistency reliability, outer loading, path coefficients, bootstrapping and mediation analysis. The results reported that three factors have positive relationship with employees’ performance i.e compensation & rewards, empowerment and job satisfaction. These three indicators also are being mediated by motivation on employees’ performance. Working environment and self-development opportunity have no relationship with employees’ performance and not mediated by motivation.